Ectopic Eyelid Cilia in a 15 years old Girl: A Rare Presentation - Godar, Manita Sunam; Shrestha, Ruchi; Godard, Krishna Chandra (Journal of Lumbini Medical College, 2018)
Introduction: Eyelashes are unique hair follicles normally found at the eyelid margin. The spectrum of cilial anomalies includes cilial row duplication, agenesis and ectopic placement. Ectopic cilia are the rarest of cilial anomalies. Case Report: A 15 years old girl presented with the complaints of eyeache and headache for three months. She also complained of extra lashes over left upper eyelid with secretion of tears while crying from the area of extra lashes. She was a diagnosed case of epilepsy under treatment for three months. On examination, visual acuity was 6/6p in right eye and 6/6p in left eyewith best corrected visual acuity being 6/6 with -0.25DS in both the eyes. The anterior and posterior segment findings were normal except for presence of extra bunch of cilia on the temporal side of the left upper eyelid two mm above the upperlid crease with dimpling of the underlying skin. Conclusion: Ectopic cilia,a rare congenital condition, is asymptomatic and surgical treatment can be done for cosmetic correction. DOI: https://doi.org/10.22502/jlmc.v6i2.166